Climate warming amplified the 2020 record-breaking heatwave in the Antarctic Peninsula - González Herrero, Sergi; Barriopedro Cepero, David; Trigo, Ricardo M.; Albert López-Bustins, Joan; Oliva, Marc (Communications Earth & Environment, 2022)
We thank David Bromwich for his useful comments and discussions on this research. We want to acknowledge the contribution of the two anonymous reviewers, which provided constructive comments that helped to substantially improve the final form of this manuscript. The AEMET Antarctic program is supported by the Ministerio para la Transición Ecológica y Reto Demográfico and Ministerio de Ciencia e Innovación of the Spanish Goverment. Research activities of S.G. and M.O. are partly funded by ANTALP Research Group, Generalitat de Catalunya. S.G. is supported by the Ministerio de Ciencia e Innovación project - PID2020-116520RB-I00 (MICROAIRPOLAR2) and RTI2018-098693-B-C32 (WISE-PreP). M.O. is supported by the Ramón y Cajal Program (RYC-2015-17597) and the NUNANTAR (PTDC/CTA-GFI/32002/2017) from the Fundacao para a Ciencia e a Tecnologia of Portugal. D.B. acknowledges support from the H2020 EU project CLINT (Grant Agreement No. 101003876). R.M.T. was supported of the Portuguese Foundation for Science and Technology through the FCT - project JPIOCEANS/0001/2019 (ROADMAP). This research is part of the CSIC Interdisciplinary Thematic Platform (PTI) Clima y Servicios Climaticos (PTI-CLIMA) and POLARCSIC (PTI-POLAR) activities. February 2020 was anomalously warm in the Antarctic Peninsula region and registered one of the most intense heatwaves ever recorded in Western Antarctica. The event featured unprecedented regional mean temperature anomalies (+4.5 degrees C) over the Antarctic Peninsula between 6 and 11 February 2020 and the highest local temperature of the continental Antarctic region. Taking flow analogs of the event from past (1950-1984) and recent (1985-2019) periods of the ERA5 reanalysis, here we quantify the role of recent climate change in the magnitude of this 6-day regional heatwave. Results show that 2020-like heatwaves over the Antarctic Peninsula are now at least similar to 0.4 degrees C warmer than in the past period, which represents a similar to 25% increase in magnitude. Given the observed ...